Assessing Seasonal Variations in Reservoir Water Quality: Implications for Eutrophication and Pollution Management - Nurdin; Agatha Sih Piranti; Sri Lestari; Iing Nasihin; Nina Herlina (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Surface water is a strategic freshwater reserve that meets the needs of households, agriculture, livestock, industry, and research. Surface water quality is affected by anthropogenic activities and seasonal variations, which can pose ecological risks. This study aimed to assess the water quality of the Darma Reservoir, the status of water quality and trophic levels, and trends in water quality changes in the rainy and dry seasons. The study was conducted for one year, from October 2023 to September 2024, covering the rainy and dry seasons. Sampling was carried out at eight stations spread across three zones of the Darma Reservoir, namely the inlet zone, utilization zone, and outlet zone. Water quality parameters were tested using PCA, the water sample measurements were compared with water quality standards (PP/22/2021), and the Regulation of the Minister of State for the Environment number 28 of 2009 was analyzed using the STORET index. The results of the study showed differences in water quality characteristics between seasons, where the concentration of Total Nitrogen (TN) showed an increase in the rainy season, while the concentration of Total Phosphate (TP) was higher in the dry season.